Conceptualising quality following conflict: Afghanistan's higher education policy. Issue 4 (30th September 2019) - Couch, Daniel
Abstract : Purpose: The purpose of this paper is to examine the dominant conceptualisation of quality in Afghanistan's higher education strategic planning and policies, and consider the implications a broader conceptualisation of quality might have within Afghanistan's conflict-affected context. Design/methodology/approach: Drawing on data from document analysis and semi-structured interviews, the author identifies the dominant policy conceptualisation of quality. Findings: The dominant conceptualisation of quality in Afghanistan's higher education policy documents aligns with the sector's primary policy purpose of promoting economic growth. However, quality assurance processes were developed with significant input from international actors, and replicate global norms for quality assurance. Whilst this is important for validity and legitimacy, at the same time it can be delegitimising for local stakeholders, and can limit opportunities for conceptualisations of quality which genuinely engage with the particularities of Afghanistan's broader conflict-affected social context. Research limitations/implications: Introducing conceptualisations of quality in Afghanistan's higher education policy which de-centre economic growth, and rather re-position social goals of cohesion and political sustainability as a central understanding of quality higher education, opens possibilities for the sector's contribution towards national development. Originality/value: There is limited published research into conceptualisations of quality within low-income and conflict-affected higher education contexts in general, and Afghanistan in particular. This paper intends to extend a critical conversation about the non-economic dividends a quality higher education sector can offer in such contexts.